Opsoclonus. Pattern of regression in a child with neuroblastoma. - Savino, P J (1975)
A child with opsoclonus associated with occult neuroblastoma is presented, in whom regression of the eye movement disorder through phases of flutter and dysmetria was observed. It is speculated that these ocular motor abnormalities represent a continuum of cerebellar dysfunction. A peculiar dysmetric head movemment not related to saccadic palsy is documented.